Partisipasi Masyarakat Dalam Pembentukan Perundang-Undangan Dalam Koherensi Teori Pembentukan Undang-Undang - Si Yusuf Al Hafiz (Lembaga Pengembangan Kinerja Dosen, 2023)
There was a clear mission and goal when this law was created. The goals and objectives set are not just the product of legislative ideas but rather goals and targets that can be accepted and supported by the entire community. There are several conditions, namely: these regulations must: (1) be implemented correctly (2) be enforced as intended (3) not deviate from applicable principles and (4) support community goals. This scientific work research is normative legal research (normative juridical). This study examines community involvement in drafting laws discussed in normative juridical research and using the theory of law formation according to Philipus M. Hadjon, Aan Seidman, Robert B. Seidman, and Nalin Abeyserkere, Meuwissen, and Hans Kelsen and Hans Nawiasky. The main characteristic of direct political involvement is direct interaction between citizens and decision-makers, not through representative procedures. If a community-friendly Job Creation Law is to be designed, it must undergo review. Legislative laws are formed in large part by a multitude of elements that are fundamental to both national and state life. The principles of clarity, fairness, and usefulness are usually found in laws created through community involvement and oversight. In contrast, less participatory and adaptable regulations may conflict with principles of social benefit and justice.